Gender research in the CGIAR Research Program on Climate Change, Agriculture and Food Security - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
This poster was presented by Sophia Huyer (CCAFS), as part of the Gender Research Coordinators' meeting (4 December 2017), related to Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.